1979
DOI: 10.1021/ja00517a044
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor agents from the bohemic acid complex. 4. Structures of rudolphomycin, mimimycin, collinemycin, and alcindoromycin

Abstract: The structures of four new anthracyclines (rudolphomycin (11), collinemycin (12), mimimycin (13), alcindoromycin ( 14)) have been determined by a combination of chemical degradations and spectral interpretation. The use of ,3C NMR spectroscopy has been extensive and assignments to the 13C NMR spectra of these compounds have been made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…A larger diaxial coupling ( J 1,2 = 8.2 Hz) was observed in the 1 H NMR spectrum of α,β‐ 7 , indicating a β‐configuration at C1. The α‐configuration of the rednose unit was assigned by analogy to the literature . In both α,α‐ 7 and α,β‐ 7 , C1′‐H appeared as a singlet in the 1 H NMR spectrum, indicative of a pseudoequatorial orientation and thus the rednose unit was concluded to be α‐configured in both disaccharides.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…A larger diaxial coupling ( J 1,2 = 8.2 Hz) was observed in the 1 H NMR spectrum of α,β‐ 7 , indicating a β‐configuration at C1. The α‐configuration of the rednose unit was assigned by analogy to the literature . In both α,α‐ 7 and α,β‐ 7 , C1′‐H appeared as a singlet in the 1 H NMR spectrum, indicative of a pseudoequatorial orientation and thus the rednose unit was concluded to be α‐configured in both disaccharides.…”
Section: Resultsmentioning
confidence: 66%
“…It was envisioned that the asymmetric reduction of 3A5AF to the acetamidofurfuryl alcohol 2 would set the scene for a new application of the Achmatowicz rearrangement (Scheme ) , . Oxidative ring expansion of 2 would result in the 2‐amino sugar N ‐acetyl‐ l ‐rednose (RedNAc, 3 ); acetamide hydrolysis would subsequently afford l ‐rednose, a trideoxysugar containing a rare β‐aminoenone unit first found in rudolphomycin, an anthracycline present in the Actinosporangium ‐derived bohemic acid complex (Figure ) . l ‐Rednose is also found in the closely related Streptomyces ‐derived anthracyclines CG21‐C, aclacinomycin X, 11‐hydroxyaclacinomycin X, and the recently reported angucycline antibiotics saquayamycins H and I .…”
Section: Introductionmentioning
confidence: 99%
“…The 4 That spectral data, coupled with the 1 H and 13 C NMR chemical shifts, indicated the presence of an anthraquinone moiety containing three phenolic groups. In addition to the fourteen signals that could be assigned to the anthraquinone system, a single anomeric signal at δ C 101.9 suggested that 1 was also a mono-glycoside.…”
Section: Resultsmentioning
confidence: 98%
“…The FT-IR spectra (Figure 3) of C indicated the presence of an ester carbonyl (1730 cm -1 ) and a hydrogen bonded carbonyl (1600 cm -1 ) group which are characteristic of epelmycin anthracyclines (Johdo et al 1991b). Also the absence of non-chelated carbonyl absorption (1670 cm -1 ) gave an indication that the aglycone could be ε-RMN rather than aklavinone (Doyle et al 1979). Therefore this Rhodosaminosyl-decyfucosyl ε-rhodomycinone could be an Epelmycin as reported by Johdo et.…”
Section: Resultsmentioning
confidence: 99%